2021
DOI: 10.1109/tnsm.2021.3073841
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Operator Connectivity Sharing for Reliable Networks: A Data-Driven Risk Analysis

Abstract: A key distinction between today's and future networks is the appetite for reliable communication to support emerging critical-communication services. In this paper, we study multi-operator connectivity as a form of redundancy to support the design of reliable networks and investigate its trade-offs. This approach is motivated by 3GPP standardisation initiatives of dual-connectivity and similar techniques in industrial wired networks. We deploy a risk awareness performance metric to assess reliability: this sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It involves the sharing of spectrum, core networks, radios, base stations, backhaul, telecommunication sites, ducts, masts, towers, equipment rooms, power supplies, air conditioning, and security systems. This method involves end-to-end network sharing (at all passive and active lev-els, including spectrum) among the slice tenants [8], [14], [56]. Unlike the previously articulated sharing strategies, the potential operators would have a network agreement only with the 5G NHN infrastructure operator.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It involves the sharing of spectrum, core networks, radios, base stations, backhaul, telecommunication sites, ducts, masts, towers, equipment rooms, power supplies, air conditioning, and security systems. This method involves end-to-end network sharing (at all passive and active lev-els, including spectrum) among the slice tenants [8], [14], [56]. Unlike the previously articulated sharing strategies, the potential operators would have a network agreement only with the 5G NHN infrastructure operator.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unlike the previously articulated sharing strategies, the potential operators would have a network agreement only with the 5G NHN infrastructure operator. This strategy also allows other potential slice tenants along with the operators to use the network [14], [59]. The key challenges of this strategy are similar pricing plans, a shift in competition, pricing strategies, resource allocation, and security of data on their slice [60]- [62].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1d shows the network architecture for a NHN strategy which involves the sharing of spectrum, core networks, radios, base stations, backhaul, telecommunication sites, ducts, masts, towers, equipment rooms, power supplies, air conditioning, and security systems. This method involves end-to-end network sharing (at all passive and active levels, including spectrum) among the slice tenants [6], [12], [71]. Unlike the previously articulated sharing strategies, the potential operators would have a network agreement only with the 5G NHN infrastructure operator.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A new cross-layer resilience scheme is proposed to address the shadowing effect. Network sharing through multi-operator connectivity is explored as a means to enhance network reliability in [25]. Using a real-world dataset, the result analysis showed that allowing mobiles with weak signalto-noise (SNR) ratio to multi-connect leads to a reliability increase for mobile operators.…”
Section: G Wireless and Mobile Network Resiliencementioning
confidence: 99%